170k views
4 votes
Which equation can be solved using the expression (-3)+-/(3)^2+4(10)(2) divided by 2(10) for x?

a)10x2 = 3x + 2
B)2 = 3x + 10x2
C)3x = 10x2 – 2
D)10x2 + 2 = –3x

User RvanDalen
by
6.4k points

1 Answer

3 votes

Answer: B

Explanation:


\frac{-(3) +/- \sqrt{(3)^(2)-4(10)(-2)}}{2(10)}

is a quadratic formula where a = 10, b = 3, and c = -2

⇒ 10x² + 3x - 2 = 0

Now let's look at the options provide and put them in standard form:

a) 10x² = 3x + 2

10x² - 3x - 2 = 0

This is NOT the same as our answer above

b) 2 = 3x + 10x²

0 = 10x² + 3x - 2

This IS the same as our answer above!!!

No need to check C and D because we already found the answer.

User Wonder
by
6.3k points